Chekhov’s 'Little Woman': Exploration of Gender Roles and Family Values in 19th Century Literary Traditions - Dimitruk, Elena; Buchelnikova, Anna; Indarti, Titik; Pairin, Udjang (Journal of Education Research, 2025)
This study examines the representation of the "little woman" in Anton Chekhov’s short stories, focusing on the interplay of gender roles and family values in 19th century Russian society. Through a literary sociology approach, the analysis explores how Chekhov’s female characters navigate societal expectations, internal conflicts, and familial responsibilities, offering a nuanced portrayal of women that diverges from traditional literary archetypes of his time. Unlike previous studies, which often generalize Chekhov’s female characters as passive or one-dimensional, this research highlights the complexity and agency of women in stories such as "The Lady with the Dog," "The Darling," and "The Schoolmistress." By analyzing narrative structure, character development, and social context, the study reveals how Chekhov critiques patriarchal norms while simultaneously depicting the emotional and psychological depth of his female protagonists. The findings demonstrate that Chekhov’s "little women" are not solely symbols of sacrifice or victimhood but are multifaceted individuals grappling with identity, autonomy, and societal constraints. The study’s novelty lies in its comparative framework, which situates Chekhov’s work alongside other literary traditions of the period, underscoring his unique contribution to the portrayal of women. By emphasizing the psychological and social dimensions of his female characters, this research contributes to literary gender studies and offers insights into the enduring relevance of Chekhov’s work in contemporary discussions on women’s roles in society. The findings invite further exploration of how classic literature can inform modern debates on gender equality and personal identity.